2019
DOI: 10.1021/acs.energyfuels.9b02305
|View full text |Cite
|
Sign up to set email alerts
|

Toward Stable Operation of Sewage Sludge Incineration Plants: The Use of Alumina Nanoparticles to Suppress Adhesion of Fly Ash

Abstract: In sewage sludge incineration plants, fly ash can adhere to the surfaces of both the incinerator and dust filter and then accumulate over time. Since this grown layer can potentially block the gas flow and damage the filter, thus preventing stable and long-term operation of incineration plants, fly ash adhesion must be monitored carefully and suppressed as much as possible. Herein, we used three different fly ash samples to demonstrate that the merger of experimental and theoretical approaches enabled a ration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 17 publications
(18 reference statements)
1
22
0
Order By: Relevance
“…39−41 For sewage sludge incinerated ashes, which contained P at high concentrations, adhesiveness began to increase near 600 °C, a temperature that is lower than that of coal ashes. 40,41 This observation indicated that the adhesiveness of ashes that contain P easily adhere inside the incineration machinery. These provided a promising method for quantifying the adhesiveness of P-containing ashes at high temperatures.…”
Section: ■ Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…39−41 For sewage sludge incinerated ashes, which contained P at high concentrations, adhesiveness began to increase near 600 °C, a temperature that is lower than that of coal ashes. 40,41 This observation indicated that the adhesiveness of ashes that contain P easily adhere inside the incineration machinery. These provided a promising method for quantifying the adhesiveness of P-containing ashes at high temperatures.…”
Section: ■ Introductionmentioning
confidence: 88%
“…A device to evaluate the adhesiveness of particles at high temperatures was developed previously and could measure the adhesiveness of many types of particulate materials, including combustion and incineration ashes. An analysis of various ashes revealed that P, Na, and K in ashes increased adhesiveness at high temperatures. For sewage sludge incinerated ashes, which contained P at high concentrations, adhesiveness began to increase near 600 °C, a temperature that is lower than that of coal ashes. , This observation indicated that the adhesiveness of ashes that contain P easily adhere inside the incineration machinery. These provided a promising method for quantifying the adhesiveness of P-containing ashes at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies had shown that the ash adhesion strength was mainly caused by the liquid phase produced by partial particle melting. [27][28][29] The liquid phase connects the particles with other solid surfaces (heating surface or other particles) to generate liquid bridging force and promote the adhesion strength of ash. In order to discuss the particle melting behavior at different temperatures, a HSML was used to test and obtain the sample shrinkage curves at high temperatures.…”
Section: Shrinkage Curve and Thermodynamic Calculationmentioning
confidence: 99%
“…Next, Al 2 O 3 nanoparticles were added to the synthetic ashes that exhibited a high tensile strength at 900 °C, and the tensile strength of the powder bed was then measured at 900 °C. It was previously shown that the addition of Al 2 O 3 nanoparticles could effectively decrease the tensile strength of coal and sewage sludge combustion ashes that showed high adhesiveness at high temperatures. One cause for the increase in adhesiveness at high temperatures of these combustion ashes could be the presence of Na and/or K, and the addition of Al 2 O 3 nanoparticles to synthetic ashes that include Na and/or K could help in mechanistically elucidating any chemical effect of Al 2 O 3 addition on the decrease in adhesiveness …”
Section: Resultsmentioning
confidence: 99%
“…We have developed a tensile strength tester for powder beds under high-temperature conditions, which has allowed for the direct evaluation of adhesiveness in a powder bed . The tester was effectively used to analyze the adhesiveness of ash powder beds collected from commercial combustion plants at high temperatures. Furthermore, it was clarified that the addition of aluminum oxide (Al 2 O 3 ) nanoparticles to coal ash and sewage sludge ash could effectively suppress the increase in particle adhesiveness; these results could contribute to the realization of highly efficient energy recovery in combustion processes. However, the details of adhesiveness at high temperatures, especially the chemical composition of ashes, remain unclear, because the combustion ashes have complex chemical components and physical properties such as porosity, which also affect the tensile strength of powder beds. ,, We have developed a synthetic ash strategy that employs a synthetic ash synthesized from a stable base material such as silicon oxide (SiO 2 ) and a target element that has the potential to increase particle adhesiveness, such as Na and K (Figure ). This strategy is a powerful tool to understand the chemical effect on adhesiveness because synthetic ashes have almost uniform physical properties, and the chemical components are simple and controllable.…”
Section: Introductionmentioning
confidence: 99%